Studies on the selective lysis and purification of Trypanosoma cruzi (The Rockefeller University Press, 1975)
The mechanism by which culture forms of Trypanosoma cruzi are lysed by normal mammalian sera was examined. Lysis is restricted to the epimastigote form of the organism and is not dependent on the presence of agglutinins. Lysis is a complement-dependent process, the activity being generated by the alternate pathway. The selective lysis by serum was exploited to purify viable trypomastigotes by means of centrifugation in an albumin column. Essentially pure trypomastigote populations are now being employed in cell culture experiments.